2001
DOI: 10.1161/01.atv.21.4.603
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein, Fibrin D-Dimer, and Incident Ischemic Heart Disease in the Speedwell Study

Abstract: Abstract-Plasma levels of C-reactive protein (CRP, a marker of the reactant plasma protein component of the inflammatory response) and of fibrin D-dimer (a marker of cross-linked fibrin turnover) have each been associated in recent studies with the risk of future ischemic heart disease (IHD). Previous experimental studies have shown that fibrin degradation products, including D-dimer, have effects on inflammatory processes and acute-phase protein responses. In the Speedwell Prospective Study, we therefore meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
138
1
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(160 citation statements)
references
References 39 publications
15
138
1
6
Order By: Relevance
“…Platelet-derived microparticles transport arachidonic acid to endothelial cells and induce the expression of cyclooxygenase 2 and the increased production of prostacyclin (43), enhance the interaction between monocytes and endothelial cells (44), and enhance leukocyte aggregation and their accumulation on the endothelium (45). Furthermore, thrombin, factor Xa, and fibrin degradation products are all potent inducers of the inflammatory response (46)(47)(48)(49)(50). Hence, the presence of microparticles in synovial fluid may facilitate not only coagulation, but also inflammation via direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-derived microparticles transport arachidonic acid to endothelial cells and induce the expression of cyclooxygenase 2 and the increased production of prostacyclin (43), enhance the interaction between monocytes and endothelial cells (44), and enhance leukocyte aggregation and their accumulation on the endothelium (45). Furthermore, thrombin, factor Xa, and fibrin degradation products are all potent inducers of the inflammatory response (46)(47)(48)(49)(50). Hence, the presence of microparticles in synovial fluid may facilitate not only coagulation, but also inflammation via direct and indirect mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…9 -11 We recently hypothesized that plasma levels of CRP and D-dimer and their associations with incident IHD in the general population might be linked, possibly caused by vessel wallrelated fibrin turnover producing D-dimer and other fibrin degradation products, which stimulate an inflammatory response including CRP. 6 In an analysis of stored plasma samples from 1690 men in the Speedwell Study of IHD risk, we observed that CRP was associated with D-dimer; both were associated with incident IHD after follow-up for 75Ϯ4 months; and that each blood measure reduced the strength of the association of the other blood measure with incident IHD. 6 We suggested that further larger studies were required to assess their relative predictive value.…”
mentioning
confidence: 92%
“…6 In an analysis of stored plasma samples from 1690 men in the Speedwell Study of IHD risk, we observed that CRP was associated with D-dimer; both were associated with incident IHD after follow-up for 75Ϯ4 months; and that each blood measure reduced the strength of the association of the other blood measure with incident IHD. 6 We suggested that further larger studies were required to assess their relative predictive value. We therefore assayed CRP in stored plasma samples from the Caerphilly Study of IHD 12 (which shares a common protocol with the neighboring Speedwell Study) and report a combined analysis of CRP, D-dimer, and incident IHD in an extended follow-up (averaging 90 months) of the combined Caerphilly-Speedwell cohort, comprising 4453 men, of whom 473 had major IHD events.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…On the contrary, Helmersson et al have reported that although smoking status correlated with a significant elevation in levels of IL-6 and serum amyloid protein A, another acute phase protein, the increase in CRP levels observed in smokers was not found to be statistically significant 29 . A dose dependent correlation between CRP and smoking habits was demonstrated in the 'Speedwell' survey of British men with respect to CRP levels which increased proportionately with the increase in number of cigarettes smoked 30 .…”
Section: Discussionmentioning
confidence: 89%